Annexation in right-wing Israeli discourse—The case of Ribonut - Lustick, Ian S. (Frontiers in Political Science, 2022)
The one-state reality has dramatically changed the discursive landscape of the movement of Israeli settlers and their supporters who have waged a half century campaign to prevent territorial compromise as a basis for Israeli-Palestinian peace. Analysis of the discourse of the Sovereignty movement, as reflected in the pages of its journal, Ribonut, traces these changes and highlights the new challenges posed to the annexationist project by the prospect of the attainability of its goals and the necessity to confront the “Arab problem.”